2008
DOI: 10.1097/ss.0b013e3181847ed6
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Soil Trivalent Chromium to Wheat Seedlings Evaluated by Chelating Resin Extraction Method

Abstract: A pot experiment of wheat seedlings with the chelating exchange resin Chelex 100, which is used to extract trivalent chromium (Cr [III]) from the soils, was conducted to examine the phytotoxicity of Cr(III)-spiked soils. Plant height and dry weight of the wheat seedlings were adversely affected by the Cr(III)-spiked acidic soils, whereas growth inhibition of wheat seedlings was not found in alkaline soils with the same quantities of added Cr(III). The concentrations of Cr in plant tissues corresponding to 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…After each wetting-drying cycle, the air-dried soils were ground, passed through a 2 mm sieve, and mixed thoroughly for the next wettingdrying cycle. The preparation of Cr(VI)-spiked soils through three wetting-drying cycles, which had been tested in our previous study (Chen et al 2008), could ensure that the Cr(VI) added in each soil sample was homogeneously mixed. After three wetting-drying cycles, the Cr(VI)-spiked soil samples were ground and sieved through a 40 mesh sieve and stored under room temperature until further use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After each wetting-drying cycle, the air-dried soils were ground, passed through a 2 mm sieve, and mixed thoroughly for the next wettingdrying cycle. The preparation of Cr(VI)-spiked soils through three wetting-drying cycles, which had been tested in our previous study (Chen et al 2008), could ensure that the Cr(VI) added in each soil sample was homogeneously mixed. After three wetting-drying cycles, the Cr(VI)-spiked soil samples were ground and sieved through a 40 mesh sieve and stored under room temperature until further use.…”
Section: Methodsmentioning
confidence: 99%
“…Sule and Ingle (1996) suggested that the Chelex 100 resin has high affinity for Cr(III) at pH 4-5 and thus it might be useful for measuring available Cr(III) in acid soils. In a previous study (Chen et al 2008), the amount of extractable soil Cr(III) by Chelex 100 was found to be highly negatively correlated with the plant height of wheat seedlings. A dose-response curve between Chelex-100 resin extractable Cr(III) and the relative plant height suggests that resin-extractable Cr(III) can be used as an index for assessing the phytotoxicity of Cr(III) in soil.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Chelex 100 resin (with a particle size ranging from 297 to 840 mm) was also washed with 1 M HCl and immersed in deionized water for 2 d. Chelex 100 resin was saturated using 2 M calcium chloride (CaCl 2 ) to convert it into the Ca-saturated form. The calcium (Ca)-saturated Chelex 100 resin was retained in 60 mesh PP bags (Chen et al 2008).…”
Section: Xanes For Soil Cr(vi) Analysismentioning
confidence: 99%
“…Therefore, lime application might raise the availability of Cr(VI) in soils and increase the phytotoxicity of Cr in Cr(VI)-contaminated soils by hindering Cr(VI) reduction and enhancing Cr(VI) desorption. On the other hand, liming might reduce the availability of Cr(III) that is formed from Cr(VI) reduction in soils and thus decrease the contribution of Cr(III) to the injury of plants in acid soils (Chen et al 2008). Therefore, the effect of liming on Cr phytotoxicity in acidic Cr(VI)-contaminated soils is worthy of investigation.…”
Section: Introductionmentioning
confidence: 99%